2007
DOI: 10.1128/mcb.00798-07
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Slowdown Mediates Translational Arrest during Cellular Division

Abstract: Global mRNA translation is transiently inhibited during cellular division. We demonstrate that mitotic cells contain heavy polysomes, but these are significantly less translationally active than polysomes in cycling cells. Several observations indicate that mitotic translational attenuation occurs during the elongation stage: (i) in cycling nonsynchronized cultures, only mitotic cells fail to assemble stress granules when treated with agents that inhibit translational initiation; (ii) mitotic cells contain few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 35 publications
7
109
1
Order By: Relevance
“…It is suggested that the highly sulfated chitosan mainly affected the intrinsic pathway, and has little effect on the assays reflecting extrinsic pathway. The results of the present study were dissimilar on Scanthophagus argus venom also not shown any disturbance in the plasma clotting time [22]. But, similar to protease from Vipera labetina [23], Naja naja [24], Naja melanolenca, Naja pallid, Crotalus argus atrox venom prolonged the coagulation of citrated plasma and shown the anticoagulant activity [25].…”
Section: Anticoagulant Activitymentioning
confidence: 96%
“…It is suggested that the highly sulfated chitosan mainly affected the intrinsic pathway, and has little effect on the assays reflecting extrinsic pathway. The results of the present study were dissimilar on Scanthophagus argus venom also not shown any disturbance in the plasma clotting time [22]. But, similar to protease from Vipera labetina [23], Naja naja [24], Naja melanolenca, Naja pallid, Crotalus argus atrox venom prolonged the coagulation of citrated plasma and shown the anticoagulant activity [25].…”
Section: Anticoagulant Activitymentioning
confidence: 96%
“…The approaches used differed both in terms of obtaining mitotic cells (release from aphidicolin-or thymidine-induced S-phase block versus mitotic shake-off) and the procedure used to study eEF2 phosphorylation (analysis with a phospho-specific antibody versus 2D gel electrophoresis, as the phosphorylation site in eEF2 (Thr56) had not been identified at that time). While this paper was under review, it was reported (Sivan et al, 2007) that eEF2 phosphorylation was elevated in cells in M-phase, although it was not explained how the synthesis of specific polypeptides could continue in mitotic cells if elongation is inhibited. Our data do provide an explanation for this, by showing that eEF2 is unphosphorylated in mitotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, slower elongation rates have been associated with the accumulation of heavier polysomes both in yeast and mammals (Hovland et al, 1999;Shenton et al, 2006;Sivan et al, 2007). As a result, mRNAs densely covered with ribosomes might be protected from degradation by nucleases, becoming more stable (Deana and Belasco, 2005;Dreyfus, 2009).…”
Section: The Absence Of Cp-trna Arg (Icg) Slows Down Chloroplast Tranmentioning
confidence: 99%